2016
DOI: 10.1002/ar.23457
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis of the middle ear ossicles and spatial relationships with the external and inner ears during the embryonic period

Abstract: We describe the three-dimensional morphogenesis of the middle ear ossicles (MEOs) according to Carnegie stage (CS) in human embryos. Seventeen samples including 33 MEOs from CS18 to 23 were selected from the Kyoto Collection. The primordia of the MEOs and related structures were histologically observed and three-dimensionally reconstructed from digital images. The timing of chondrogenesis was variable among structures. The stapes was recognizable as a vague condensation of the mesenchymal cells in all samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
0
10
0
3
Order By: Relevance
“…Mesenchyme in the first pharyngeal arch seems to form the incus as well as Meckel's cartilage, but the origin of the first pharyngeal arch should not be considered equivalent to the origin of Meckel's cartilage. According Ozeki-Satoh et al 2016, the incus was no contiguous with the malleus at CS 19.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchyme in the first pharyngeal arch seems to form the incus as well as Meckel's cartilage, but the origin of the first pharyngeal arch should not be considered equivalent to the origin of Meckel's cartilage. According Ozeki-Satoh et al 2016, the incus was no contiguous with the malleus at CS 19.…”
Section: Discussionmentioning
confidence: 99%
“…This study is the first observe the initiation of TC formation using 3D imaging methods. Our previous study involving histological sections revealed that the handle of the malleus approached the tubotympanic recess—which later differentiates into the TC—while remaining distant from the external auditory meatus at CS23 (Ozeki‐Satoh et al, ). In samples exhibiting a CRL of 86 mm, the recess contained a thin yet distinct cavity attached to the external auditory meatus on the convex surface, which later developed into the tympanic membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The os goniale becomes ossified between 26.5 and 34 mm CRL, corresponding to CS23 or later. Previously, we detected the os goniale in histological sections, as this structure is too thin to observe using MRI or phase‐contrast computed tomography (CT) due to limitations in resolution (Ozeki‐Satoh et al, ). Previous studies have reported attachment of the anterior process to the main region in fetuses with a CRL of 120 mm (Richany et al, ), 85 mm, and 93 mm (Rodríquez‐Vázquez et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… [1] Nakashima et al , [2] Kobayashi et al , [3–5] Shiraishi et al , [6] Shiraishi et al , [7] Taketani et al , [8] Yoshida et al, in press, [9] Takakuwa et al, , [10] Mehemed et al, , [11] Kishimoto et al, , [12,13] Toyoda et al, , [14] Kagurasho et al, , [15] Ozeki‐Sato et al, a, [16] Ozeki‐Sato et al, , [17] Osaka et al, , [18] Ueno et al, , [19] Kaigai et al, . [20] Nako et al, , [21] Ueda et al, , [22,23] Hirose et al, , 2016, [24] Hamabe et al, , [25] Kanahashi et al, , [26] Endo et al, , [27] Takakuwa et al, , [28] Shiraishi et al, .…”
Section: Methodsmentioning
confidence: 99%